Effect of Combined Oral Contraceptive Pill on Serum Bilirubin and Alkaline Phosphatase - Rupa, Shamima Nazneen; Begum, Bedowra; Jolly, Sayeeda Sultana; Kabir, Farjana; Akhter, Shahnaz; Khan, Zahid Hasan; Nath, Manik Chandra (TAJ: Journal of Teachers Association, 2023)
Background: Combined oral contraceptive is the most known and popular method of contraception. The combined oral contraceptive pill was the first oral contraceptive method and was commercially marketed in 1960. Earlier investigators reported that early oral contraceptive pills had many side effects. Despite the modifications on early OCPs in terms of content and dosage to lessen their side effects, newer contraceptives still have some hepatotoxic effects. Aim and Objectives: The objective of this study was to investigate the effect of low-dose OCP on S. bilirubin and ALP- one of the most important liver enzymes. Materials and Methods: This cross-sectional analytical study was conducted on 184 healthy women aged 20-45. Among them, 92 women were OCP users, and 92 were nonusers. BMI-matched non-OCP users women were recruited in the study for comparison of S. bilirubin and ALP. A systematic sampling technique was applied to select each respondent. Data collection was commenced after obtaining ethical clearance from the Ethical Committee and informed consent from the respondents. Results: The Results showed a significant decrease in serum Alkaline phosphatase among OCP users (p=0.001), but the ALP level was progressively increased with increased duration of OCP use. Serum bilirubin level was within the normal range, but the levels were slightly higher in OCP users but in. OCP users' serum bilirubin levels did not significantly increase with the duration of OCP use (P > 0.05). In summary, OCP users' women are associated with a decreased level of serum Alkaline phosphatase and a slightly increased level of serum bilirubin. Conclusion: So regular monitoring of S. bilirubin and ALP should be done among OCP users women to avoid many unwanted complications. TAJ 2022; 35: No-2: 133-141